Virally-initiated pain states: phenotypes, mechanisms, and future directions - Sara A. Dochnal; Steven P. Cohen; Mark R. Hutchinson; Mark R. Hutchinson; Mark R. Hutchinson; Yury I. Miller; Tony L. Yaksh (Frontiers in Pain Research)
The recent SARS-CoV-2 pandemic has underscored the significance of viral infections, affecting billions of lives and costing trillions of dollars globally. Even beyond SARS-CoV-2, common infections with viruses like influenza, HIV, and herpesviruses have profound impacts beyond their typical manifestations, often triggering acute and chronic pain syndromes that can be life-altering. These virally induced pain states can arise through direct viral replication within neurons, or indirectly, via immune responses to infection in both the contexts of afferent signaling in the dorsal root ganglion (DRG) or subsequent higher order integration in intracranial systems. Varicella-zoster virus (VZV), influenza virus, and SARS-CoV-2 each provide a unique lens through which to examine the interplay between viral activity and pain. This perspective paper is not meant to be an exhaustive review of virally-induced neuropathic pain states. It seeks to explore curated aspects of the complexities of these pain states, identify research gaps, and suggest solutions using nanoscale molecular understanding and psychoneuroimmunological and biopsychosocial frameworks. Each subheading is accompanied by a list of related issues for study which we think will lead to advances in our understanding of the vexing pain phenotype associated with viral infection.